2004
DOI: 10.1002/mrm.20227
|View full text |Cite
|
Sign up to set email alerts
|

Defining a local arterial input function for perfusion MRI using independent component analysis

Abstract: Quantification of cerebral blood flow (CBF) using dynamic-susceptibility contrast MRI relies on the deconvolution of the arterial input function (AIF), which is commonly estimated from the signal changes in a major artery. However, it has been shown that the presence of bolus delay/dispersion between the artery and the tissue of interest can be a significant source of error. These effects could be minimized if a local AIF were used, although the measurement of a local AIF can be problematic. This work describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
178
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(181 citation statements)
references
References 20 publications
3
178
0
Order By: Relevance
“…Researchers have proposed several methods to remedy such difficult situations. For example, a local AIF was proposed to improve the accuracy of quantification (29). An experimentally derived AIF is used for regions in which the measurement of AIF is not possible (25).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have proposed several methods to remedy such difficult situations. For example, a local AIF was proposed to improve the accuracy of quantification (29). An experimentally derived AIF is used for regions in which the measurement of AIF is not possible (25).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the various steps involved in the method can be found in Ref. 11. Using this methodology, the local AIF generated in patients with various cerebrovascular abnormalities was found to display regional heterogeneity, with areas having delayed bolus arrival and wider peaks that were consistent with the patients' vascular abnormalities (e.g., see Fig.…”
Section: Minimization Of the Dispersion Processmentioning
confidence: 99%
“…Alternatively, it has been suggested that local or regional AIF measurements can improve determination of the perfusion parameters (5)(6)(7)(8)(9)(10)(11). These local AIFs are measured closer to the capillaries of the brain tissue compared to global AIF measurements.…”
mentioning
confidence: 99%
“…However, blood sampling cannot be performed at that point in the brain-vasculature. Therefore, previous validations of local AIF measurements have been performed by comparing the perfusion maps (and sometimes the CTCs) from local AIF measurements to those obtained from manually selected global AIF measurements (8)(9)(10)20,21). A single report showed additional comparison to PET perfusion maps (20).…”
mentioning
confidence: 99%